Developing Canva-Based Interactive Multimedia with PBL Integrated into Google Forms and Liveworksheets for Elementary Indonesian Language - Disha Hikarahmi Ramfineli; Alwen Bentri; Muhammadi Muhammadi; Elfia Sukma (STAI Hubbulwathan Duri, 2025)
The integration of digital technology in elementary Indonesian language instruction remains limited, leading to monotonous learning and low student engagement, especially in the context of Society 5.0. This study aimed to develop and evaluate an interactive multimedia product based on Canva, integrated with Google Forms and Liveworksheets, and designed using the Problem-Based Learning (PBL) approach to support procedural text writing in grade IV. The research employed the ADDIE development model, involving analysis, design, development, implementation, and evaluation stages. Participants included three expert validators (material, media, language), 10 teachers in a Focus Group Discussion, and 56 fourth-grade students from three elementary schools in Padang, Indonesia. Data collection instruments included validation sheets, practicality questionnaires, and pretest-posttest learning outcomes analyzed using N-Gain and t-tests. Results showed that the developed multimedia was highly valid, with expert ratings ranging from 88.16% to 98.43% and FGD feedback averaging 97.34%. Practicality was rated very high by both teachers (94.32%) and students (95.85%). Effectiveness testing revealed a significant improvement in learning outcomes (N-Gain = 83.58%), with a t-test indicating significant differences between experimental and control groups (p 0.05). These findings demonstrate that Canva-based interactive multimedia with PBL is a valid, practical, and effective learning tool. It enhances engagement and procedural writing skills, aligning well with the demands of 21st-century and technology-integrated education.